2018
DOI: 10.1027/0227-5910/a000478
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health Professionals' Suicide Risk Assessment and Management Practices

Abstract: Although the majority of mental health professionals report using evidenced-based practices, there appears to be variability in utilization of evidence-based practices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
45
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(49 citation statements)
references
References 26 publications
2
45
1
1
Order By: Relevance
“…As hypothesized, behavioral health providers who reported being more confidence in their skills related to suicide care were also more likely to incorporate best practices. This result is in accordance with previous research that suggests that level of comfort and self-efficacy beliefs associated with working with suicidal people are related to greater use of evidenced-based practices, even when controlling for individual differences and case load (Lee, Osteen, & Frey, 2016;Osteen, Frey, Woods, Ko, & Shipe, 2017;Roush et al, 2018). In fact, one previous study found that providers with higher comfort levels, regardless of fear of negative outcomes, were more likely to adequately implement suicide risk assessments (Roush et al, 2018).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…As hypothesized, behavioral health providers who reported being more confidence in their skills related to suicide care were also more likely to incorporate best practices. This result is in accordance with previous research that suggests that level of comfort and self-efficacy beliefs associated with working with suicidal people are related to greater use of evidenced-based practices, even when controlling for individual differences and case load (Lee, Osteen, & Frey, 2016;Osteen, Frey, Woods, Ko, & Shipe, 2017;Roush et al, 2018). In fact, one previous study found that providers with higher comfort levels, regardless of fear of negative outcomes, were more likely to adequately implement suicide risk assessments (Roush et al, 2018).…”
Section: Discussionsupporting
confidence: 92%
“…One of the advantages of CAMS is that treatment is designed to be a collaborative process in which both the clinician and the client decide the focus of intervention to reduce suicidality (Ellis, Rufino, & Allen, 2017;Jobes, 2012). The empirical evidence on the effectiveness of CAMS to target suicidality is continuing to grow; for example, CAMS demonstrates effectiveness in reducing suicide ideation, overall distress, and increasing hope (Ellis, Rufino, Allen, Fowler, & Jobes, 2015;Jobes, Lento, & Brazaitis, 2012;Ryberg et al, 2016). Results suggested that all trainings but QPR were associated with greater self-report confidence on providing suicide-specific care, with AMSR being a stronger predictor of these scores.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In clinical encounters with individuals at risk for suicide, clinicians are challenged to make accurate risk assessments and critical treatment decisions while developing or maintaining a solid therapeutic alliance (American Psychiatric Association, ). Encounters with suicidal individuals (i.e., individuals who present with suicide attempts and/or ideation) are consistently reported by mental health professionals to be highly stressful (Berman, Stark, Cooperman, Wilhelm, & Cohen, ; Deutsch, ; Jahn, Quinnett, & Ries, ; Roush et al, ). Documented emotional responses to suicidal patients include feelings of anxiety, incompetence, frustration, anger, as well as helplessness, discouragement, sadness, and guilt (For recent reviews see Ellis, Schwartz, & Rufino, ; Soulié, Bell, Jenkin, Sim, & Collings, ).…”
Section: Introductionmentioning
confidence: 99%
“…In any case, the increasing trend towards the practice of defensive medicine would render decision-making based on patients' wellbeing as the main target more difficult [58,59]. On the other hand, evidence shows that one out of every three mental health professionals does not regularly ask patients about ideas or thoughts related to suicide [60]. This leads to the conclusion that mental health professionals are perhaps not as aware as they should be of their need for further training and that it could be necessary for them to improve their detection and management skills, regardless of the fact that they might not know it.…”
Section: Discussionmentioning
confidence: 99%